Projeto e implementação de uma lâmpada led bulbo em conformidade com aspectos elétricos, térmicos e ópticos exigidos pelas normativas brasileiras - Melo, Maicol Flores de (2018)
This work presents an LED bulb lamp conception aiming to replace traditional lighting technologies such as incandescent and compact fluorescent lamps. The LED lamp manufacture and sale requirements based on INMETRO Ordinance 389 and Procel and Energy Star voluntary seals are initially presented. Moreover, the work shows the current state and a coming years projection involving LED-based lighting systems. Initial approach to an LED lamp design must consider thermal, electrical and optical aspects, also known as photoelectrothermal theory. The photoelectrothermal theory is widely discussed in the literature. However, these theories require high cost equipment to perform experimental tests. This way, it is possible to emphasize as a contribution that the proposed methodology avoid experimental tests, performing the system design based only on the LED datasheet information. The photoelectrothermal design enables to define the desired lighting system specifications, always taking into account the regulations presented. To exemplify the characteristics that can be defined during the photoelectrothermal design are luminous efficacy, useful life, total luminous flux, among others. In addition, it is possible to define electronic circuit characteristics, such as LEDs amount, LEDs forward current, electrical power and others. Thus, after the photoelectrothermal design the electronic system design can be performed, which should be simple, robust, present long useful life and reduced volume. Besides a satisfactory LEDs supply, this work presents a low frequency ripple transmission analysis from bus voltage to LED current considering the power control stage. Attenuate the low frequency ripple transmission reduces the necessary bus capacitance and mitigates the LED current ripple effects in the observer health. This way, resonant series converter is analyzed and a comparative study with the Buck converter, operating in both operation modes, is performed. Experimental tests in one integrating sphere prove the feasibility of the proposed photoelectrothermal methodology. A prototype of the electronic circuit was implemented, where it is proved the satisfactory LEDs supply behavior and a positive characteristic regarding the ripple transmission by the series resonant converter, proving the proposed theory.